A 2.4-kilobase-pair fragment of the Friend murine leukemia virus genome contains the sequences responsible for friend murine leukemia virus-induced erythroleukemia. - Oliff, A (1983)
Friend murine leukemia virus (F-MuLV) is a replication-competent, ecotropic, NB-tropic retrovirus which produces a rapidly fatal erythroleukemia in susceptible strains of mice. We previously molecularly cloned the entire F-MuLV genome. Transfection of this cloned DNA into NIH 3T3 mouse fibroblasts produces a virus with the same leukemia-inducing characteristics as F-MuLV. To identify which portion of the F-MuLV genome is responsible for causing leukemia, we made recombinant viruses between subgenomic fragments of F-MuLV DNA and another retrovirus--Amphotroph clone 4070. Amphotroph clone 4070 is a replication-competent, amphotrophic, N-tropic virus which does not produce any detectable malignancy in mice. A 2.4-kilobase-pair fragment of F-MuLV DNA was isolated. This DNA fragment encompassed approximately 700 base pairs from the 3' end of the F-MuLV pol gene and 1.7 kilobase pairs of the env gene including all of gp70 and the N-terminal four-fifths of p15E. A molecularly cloned fragment of Amphotroph DNA was ligated to the 2.4-kilobase-pair F-MuLV DNA, and an 8.3-kilobase-pair hybrid F-MuLV-Amphotroph DNA was subcloned into a new plasmid (p5a25-H). Transfection of p5a25-H DNA into fibroblasts resulted in the production of a replication-competent, ecotropic, N-tropic retrovirus--5a25-H virus. Inoculation of this virus into newborn NIH Swiss mice caused leukemia within 4 to 6 months. The disease caused by 5a25-H was pathologically and histologically indistinguishable from the disease caused by F-MuLV. We conclude that the F-MuLV sequences needed to cause disease are contained in these 2.4 kilobase pairs of DNA.